(-2)^50+(-2)^49+(-2)^48+(-2)^47+...+(-2)+1(x-1)(x^3+x^2+x+1)=x^4-1用这种方法因式分解以此类推
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 06:06:59
(-2)^50+(-2)^49+(-2)^48+(-2)^47+...+(-2)+1(x-1)(x^3+x^2+x+1)=x^4-1用这种方法因式分解以此类推(-2)^50+(-2)^49+(-2)^
(-2)^50+(-2)^49+(-2)^48+(-2)^47+...+(-2)+1(x-1)(x^3+x^2+x+1)=x^4-1用这种方法因式分解以此类推
(-2)^50+(-2)^49+(-2)^48+(-2)^47+...+(-2)+1
(x-1)(x^3+x^2+x+1)=x^4-1
用这种方法因式分解
以此类推
(-2)^50+(-2)^49+(-2)^48+(-2)^47+...+(-2)+1(x-1)(x^3+x^2+x+1)=x^4-1用这种方法因式分解以此类推
设S=(-2)^50+(-2)^49+(-2)^48+(-2)^47+...+(-2)+1
2S=(-2)^51+(-2)^50+(-2)^49+(-2)^48+...+(-2)^2-2
2S-S=S=(-2)^51-1=-2^51-1
50*50-49*49+48*48.+2*2-1*1
49、50、1、2、3
计算:50/1+50/2+50/3+.+50/49
(-2)^50+(-2)^49+(-2)^48+...+(-2)+1简便运算
计算1+2+3+4+.+49+50
1+2+3+***+49+50 =
1+1+2+3+.+49+50=
1+2+3.+49+50的步骤
51+50+49+.+3+2+1=?
A+2A+3A+.+49A+50A+50B+49B+.+2B+B
计算:50^2 - 49^2 + 48^2 - 47^2 + ...+ 2^2 - 1^2
50*2-49*2+48*2-47*2+.2*2-1*2怎么计算?
1/1*2+1/2*3+.+1/49*50
1/1*2+1/2*3+.+1/49*50
1+2+3+.50+49+.+3+2+1=
1.1*2+2*3+3*4+.+49*50=
1×2+2×3+3×4+.49×50 等于几
50/1+50/2+50/3+……+50/49+50/50